Paradigma Pengelolaan Lingkungan (Antropocentric versus Ekocentric) - Husni Thamrin (Kutubkhanah, 2013)
In a few years of this decade the environmental crisis is so great for human survival. The environmental crisis is rooted in human behavior errors, and errors of human behavior is rooted in people’s thinking about himself, human nature and the relationship between the natural and social environment. How to view anthropocentric that focus heavily on the views of capitalistic, pragmatic, and economical allegedly been exploiting the environment so drastically. Moderate eco centric view that focuses on the ecological view, ethical, and it is limited in nature to understand in preserving the environment.